Imaging prostate cancer with prostate-specific membrane antigen PET/CT and PET/MRI: current and future applications - Hope, Thomas A.; Afshar-Oromieh, Ali; Eiber, Matthias (American journal of roentgenology, 2018)
Prostate-Specific Membran...Notes on InterpretationClinical ApplicationsPET/CT Versus PET/MRIFuture ApplicationsPath Toward ApprovalConclusionReferences OBJECTIVE. The purpose of this article is to describe the large number of radiotracers being evaluated for prostate-specific membrane antigen (PSMA) PET, which is becoming a central tool in the staging of prostate cancer. CONCLUSION. PSMA PET is a highly promising modality for the staging of prostate cancer because of its higher detection rate compared with that of conventional imaging. Both PET/CT and PET/MRI offer benefits with PSMA radiotracers, and PSMA PET findings frequently lead to changes in management. It is imperative that subsequent treatment changes be evaluated to show improved outcomes. PSMA PET also has potential applications, including patient selection for PSMA-based radioligand therapy and evaluation of treatment response.
Gesehen am 11.06.2019